2022
DOI: 10.3390/metabo12100909
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Proteomic Responses of Dairy Buffalo to Heat Stress Induced by Different Altitudes

Abstract: Buffalo are mainly distributed in low-altitude (LA), medium-altitude (MA), and high-altitude (HA) regions characterised by different thermal and oxygen environments in Yunnan province, China. Due to black skin, sparse hair, and the low density of skin sweat glands, buffalo are more sensitive to heat stress. Here, we used data-independent acquisition (DIA) proteomics to reveal a broad spectrum of proteins that play roles in adaptation to the heat stress of buffalo raised at low altitude or hypoxia at high altit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The results obtained for the buffaloes transported for short periods showed that the surface temperatures of thermal windows of the head and trunk increased significantly in P2, P4, P6, and P7, that is, during the events that required handling (p < 0.0001). These responses may be associated with the loss of thermal stability in the buffaloes, a species whose optimal ambient for achieving thermoneutrality is in the range of 13-18°C (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained for the buffaloes transported for short periods showed that the surface temperatures of thermal windows of the head and trunk increased significantly in P2, P4, P6, and P7, that is, during the events that required handling (p < 0.0001). These responses may be associated with the loss of thermal stability in the buffaloes, a species whose optimal ambient for achieving thermoneutrality is in the range of 13-18°C (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…However, heat stress also causes cellular and molecular responses, such as an imbalance in the production of oxidants and antioxidants, resulting in oxidative stress [ 14 ]. Heat stress has been reported to cause oxidative stress in livestock animals, including dairy cattle [ 15 ], sheep [ 16 ], pigs [ 17 ], and buffaloes [ 18 ]. Oxidative stress has been linked to several pathologies in humans, such as cardiovascular diseases, metabolic syndrome, neurodegenerative disorders, autoimmune diseases, and cancer [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, OSi reference values for buffaloes have not been reported. Furthermore, despite the fact that some studies have reported the levels of oxidants and antioxidants in buffaloes, reference values for these biomarkers have not yet been defined [ 18 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Existing research on HS has mostly focused on alleviating the accumulation of reactive oxygen species, mitigating oxidative stress and cell apoptosis in the body. [22][23][24] However, recent studies have highlighted the potential of L-theanine (LTA) to mitigate the harmful effects of HS by reducing inflammatory and oxidative stress responses. 25 As a unique non-protein free amino acid found in tea leaves, LTA is highly soluble in water.…”
Section: Introductionmentioning
confidence: 99%